2007
DOI: 10.1260/174795407780367140
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Leg-Kicking Training Program on Performance and Physiological Measures of Competitive Swimmers

Abstract: This study investigated the adaptations in leg muscle metabolism of swimmers following a six-week, leg-kicking swimming training program.Fifteen male competitive swimmers were randomly assigned to an experimental group (E; n=8) and a control group (C; n=7). E swimmers performed normal leg-kicking training three times per week, whereas C swimmers performed reduced leg-kicking training (20% and 4% of weekly training distance, respectively). Before and after the training program, all swimmers performed a 200 m le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
0
15
0
2
Order By: Relevance
“…If swimmers want to increase their speed, U, they should train by increasing f without decreasing A during maximal UUS. Konstantaki and Winter (2009) investigated the effect of six week leg kicking training for competitive male swimmers (an experiment group conducted a kicking training session equivalent to 20% of total training per a week, while a control group was equivalent to 4%) with randomized control design. The authors reported that 200-m kicking time of the training group was shorter (À6%) than the control group, and concluded leg-kicking swimming training could enhance exercise efficiency and improve leg endurance.…”
Section: Swimming Velocity and Kick Amplitudementioning
confidence: 99%
“…If swimmers want to increase their speed, U, they should train by increasing f without decreasing A during maximal UUS. Konstantaki and Winter (2009) investigated the effect of six week leg kicking training for competitive male swimmers (an experiment group conducted a kicking training session equivalent to 20% of total training per a week, while a control group was equivalent to 4%) with randomized control design. The authors reported that 200-m kicking time of the training group was shorter (À6%) than the control group, and concluded leg-kicking swimming training could enhance exercise efficiency and improve leg endurance.…”
Section: Swimming Velocity and Kick Amplitudementioning
confidence: 99%
“…There were similar enhancements among 25-m segments across all swimmers, suggesting that for a given change in kick rate there was a corresponding change in 25-m time, independent of fatigue. Recent findings have suggested that kicking training improves leg conditioning and is effective for inducing training adaptations (Konstantaki & Winter, 2007). Combined with the achievable increases in kick rate, coaches could use this knowledge to design kicking training programmes to increase swimming speed.…”
Section: Measurement Of Kick In Paralympic Swimmersmentioning
confidence: 99%
“…Coaches prescribe kicking-only drills in the majority of swimming training sessions but until now lap time has been the only variable quantified (Konstantaki & Winter, 2007). Difficulties in assessing characteristics of the kick can be overcome with recent developments, such as inertial-sensor technology (Fulton, Pyne, & Burkett, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A pesar del número de investigaciones realizadas en este campo, han sido diferentes los ensayos con nadadores y métodos utilizados para investigar la influencia del batido subacuático (Cohen, Cleary y Mason, 2012;Konstantaki y Winter, 2009;Loebbecke et al, 2009a;. Konstantaki y Winter (2009) mediante del entrenamiento del batido de piernas durante seis semanas y con un diseño de control aleatorio en nadadores masculinos competitivos (un grupo experimental llevo a cabo una sesión de entrenamiento del batido equivalente al 20% del entrenamiento total por una semana, mientras que un grupo de control fue equivalente al 4%).…”
Section: Técnicas De Medición Y Análisis Del Batido Subacuáticounclassified
“…Konstantaki y Winter (2009) mediante del entrenamiento del batido de piernas durante seis semanas y con un diseño de control aleatorio en nadadores masculinos competitivos (un grupo experimental llevo a cabo una sesión de entrenamiento del batido equivalente al 20% del entrenamiento total por una semana, mientras que un grupo de control fue equivalente al 4%). Ambos autores llegaron a la conclusión de que el entrenamiento del batido de pierna podría aumentar la eficacia de la prueba y mejorar la resistencia de la pierna.…”
Section: Técnicas De Medición Y Análisis Del Batido Subacuáticounclassified